Lifestyle Optimazion to Increase Interest in Purchasing Thrift Clothest among the People of Medan City - Lubis, Fauzi Arif; Aslami, Nuri; Puspita, Nina; Sitompul, Siti Nur Aisah (Universitas Islam Negeri Sumatera Utara, 2024)
This study examines the influence of consumer lifestyle on the interest in purchasing thrift clothing in Medan City. Utilizing qualitative methods, we conducted in-depth interviews with 30 consumers and thrift sellers to gather insights into how lifestyle choices impact purchasing decisions. The findings reveal that consumers perceive thrift clothing as affordable, trendy, and unique compared to regular retail options. This perception drives increased consumer interest and contributes to the growth of thrift markets. Additionally, the study highlights the importance of collaboration with local government to enhance support for thrift businesses through improved facilities and marketing strategies. By promoting the sustainability and environmental benefits of thrifting, this research aims to foster a more conscious consumer culture and strengthen the market position of thrift retailers.